Optimalisasi Pembelajaran Puasa Ramadan melalui Simulasi Ibadah untuk Menanamkan Nilai Kesabaran Siswa Kelas III SDN 04 BIRUGO Kota Bukittinggi - Zamzami Zamzami (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study examines the optimization of Ramadan fasting education through worship simulation to instill patience values in third-grade students at SDN 04 Birugo, Bukittinggi. Using a qualitative descriptive approach, data were collected via classroom observations, interviews with Islamic education teachers, and documentation of learning activities. The findings reveal that worship simulations, designed to mimic real fasting practices, significantly enhanced students' enthusiasm, understanding of Ramadan’s spiritual significance, and behavioral changes reflecting patience. Students demonstrated improved self-control, discipline, and social cooperation during and after the simulations. Teachers reported that experiential learning through simulations facilitated deeper engagement compared to conventional methods, enabling students to internalize abstract values through concrete experiences. Key recommendations include integrating simulations into Islamic education curricula, providing teacher training, and fostering parental involvement to reinforce learned values. This study highlights the effectiveness of simulation-based learning in fostering holistic religious and moral development, advocating its adoption as an innovative pedagogical tool in primary Islamic education.